2021
DOI: 10.22603/ssrr.2020-0037
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intervention for Prevention of Postoperative Delirium after Spine Surgery

Abstract: Introduction Delirium after spine surgery is an important complication; identification of risk factors associated with postoperative delirium (PD) is essential for reducing its incidence. Prophylactic intervention for PD has been reported to be effective. This study aimed to identify risk factors for PD and determine the efficacy of a prevention program using a delirium risk scoring system for PD after spine surgery. Methods This study was conducted in two stages. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The patients and their families who received an individualised education session, critical care tour and information leaflet had a lower incidence of postoperative delirium compared with those patients receiving standard care (10% vs. 24%; p = 0.038) [27]. Similarly, multi‐component interventions for the prevention of delirium may include an educational facet [28]. The potential benefit of educational interventions is reflected in the recent expert consensus paper by Peden et al.…”
Section: Prevention Of Delirium: Non‐pharmacological Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The patients and their families who received an individualised education session, critical care tour and information leaflet had a lower incidence of postoperative delirium compared with those patients receiving standard care (10% vs. 24%; p = 0.038) [27]. Similarly, multi‐component interventions for the prevention of delirium may include an educational facet [28]. The potential benefit of educational interventions is reflected in the recent expert consensus paper by Peden et al.…”
Section: Prevention Of Delirium: Non‐pharmacological Methodsmentioning
confidence: 99%
“…The strongest evidence for pharmacological delirium prevention involves medication avoidance, specifically benzodiazepines, with a two-to five-fold increased incidence of delirium in patients given peri-operative benzodiazepines [28,30].…”
Section: Avoidance Of Certain Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the elderly, benzodiazepines and z-drugs have been shown to increase the risk of hip fractures, which may be related to sedation, cognitive reduction, or impaired balance, or possibly to decreased bone density [35][36][37] . Studies have shown that patients with a history of benzodiazepine use were at a greater risk for delirium after hip fractures 38 , spine surgery 39 , or total joint arthroplasty 7 . In patients having total knee arthroplasty specifically, benzodiazepines can be associated with an increased risk of revision surgery, fractures, and delirium 40 .…”
Section: Adverse Effects and Risksmentioning
confidence: 99%
“…Secondly, it can help patients psychologically prepare for surgery. Through systematic and professional delirium 28 and that electroconvulsive therapy could also delay delirium. 29 However, the impact of preoperative visits on POD has yet to be investigated.…”
Section: Effect On the Incidence Of Podmentioning
confidence: 99%